Tafsir Komprehensif Karya Clifford Geertz: Abangan, Santri, Dan Priyayi Dalam Masyarakat Jawa - Miftakhur Ridlo (Institut Ilmu Keislaman Zainul Hasan Genggong, 2021)
Geertz has made many contributions related to the typology of Javanese society, especially in matters of religious typology. In line with that, a lot of controversy and criticism were addressed to him. This is due to the inequality of ideas conveyed, especially globalization or the universality of religious concepts in Javanese society which is represented by only one, in Modjokuto village. As a result, many new studies have spawned almost the same discussion, namely the intersection between Islam and local culture in other areas such as : Yogyakarta, Buton, Lombok and others. It is interesting when discussing the concepts of syncretism, acculturation, Islamization, and indigenization. This is due to the uniqueness of the form of Islamic meeting or processes in various regions which are relatively different. The reason is difference local wisdom and traditions that have been rooted in the community. The difference in local wisdom may be a motivation for Islamic scientists’ to further explore some of the unique traditions that may not have been raised in academic circles. Keywords: interpretations, Clifford Geertz